Critic-only adaptive dynamic programming algorithms’ applications to the secure control of cyber–physical systems - Jiang, He; Zhang, Huaguang; Xie, Xiangpeng (ISA transactions, 2020)
Industrial cyber–physical systems generally suffer from the malicious attacks and unmatched perturbation, and thus the security issue is always the core research topic in the related fields. This paper proposes a novel intelligent secure control scheme, which integrates optimal control theory, zero-sum game theory, reinforcement learning and neural networks. First, the secure control problem of the compromised system is converted into the zero-sum game issue of the nominal auxiliary system, and then both policy-iteration-based and value-iteration-based adaptive dynamic programming methods are introduced to solve the Hamilton–Jacobi–Isaacs equations. The proposed secure control scheme can mitigate the effects of actuator attacks and unmatched perturbation, and stabilize the compromised cyber–physical systems by tuning the system performance parameters, which is proved through the Lyapunov stability theory. Finally, the proposed approach is applied to the Quanser helicopter to verify the effectiveness. •Secure control problems are converted into zero-sum game issues.•Two mainstream ADP methods are introduced to solve HJI equations.•Tuning conditions of secure control parameters are derived.•The proposed control scheme is tested on the Quanser helicopter.